A rare case of primary small bowel de-differentiated liposarcoma causing intussusception: A case report. Issue 24 (June 2018) - Matsuo, Kentaro; Inoue, Masaya; Shirai, Yasutsugu; Kataoka, Tatsuki; Kagota, Shuji; Taniguchi, Kohei; Lee, Sang-Woong; Uchiyama, Kazuhisa
Abstract: Rationale: Liposarcoma (LPS) is a relatively rare malignant soft tissue tumor. Management of LPS including diagnosis is difficult, because it has no characteristic symptoms and no established effective treatment. Herein we reported an extremely rare case of intussusception induced by primary small bowel LPS. Patient's concern: A-84-year-old male was a consult to our Emergency Department with symptoms of a terrible general fatigue, abdominal pain, and vomiting. Diagnosis: Abdominal ultrasonography and computed tomography (CT) revealed probable intussusception. Interventions: After decompression by insertion of an ileus tube, surgery was performed. Outcomes: The ileum and mesentery of the small intestine had invaginated into the colon. There was no evidence of metastases in the intraabdominal space. The Hutchinson maneuver could not release the invagination, and so ileocecal resection with lymph node dissection was performed. Histopathological examination showed evidence of the growth of spindle-shaped cells. Also, immunohistochemical examination indicated the tumor to be a de-differentiated LPS. The patient was discharged on postoperative day 19 without any complications; and no recurrence of the tumor was observed at 16 months post operation. Lessons: LPS should be considered in the differential diagnosis of adult intussusception, and careful management should be required, including observation, after surgery. Abstract : Supplemental Digital Content is available in the text